2001
DOI: 10.1056/nejm200106213442504
|View full text |Cite
|
Sign up to set email alerts
|

Early Gastric Cancer in Young, Asymptomatic Carriers of Germ-Line E-Cadherin Mutations

Abstract: We recommend genetic counseling and consideration of prophylactic gastrectomy in young, asymptomatic carriers of germ-line truncating CDH1 mutations who belong to families with highly penetrant hereditary diffuse gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
241
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 376 publications
(257 citation statements)
references
References 13 publications
4
241
1
11
Order By: Relevance
“…Barber et al [68] investigated immunoreactivity of cytokeratins (CK) 8/18 and vimentin by dual-label immunofluorescence, and their results failed to demonstrate the evidence of EMT. CK expression in both differentiated and dedifferentiated SRCCs had also been described in previous studies [64,69]. Moreover, N-cadherin, an EMT marker with increased expression in the presence of EMT [73] was not observed in intramucosal foci of SRC [52].…”
Section: Immunohistochemical Profile Of Hdgc and Its Relationship Witsupporting
confidence: 80%
See 2 more Smart Citations
“…Barber et al [68] investigated immunoreactivity of cytokeratins (CK) 8/18 and vimentin by dual-label immunofluorescence, and their results failed to demonstrate the evidence of EMT. CK expression in both differentiated and dedifferentiated SRCCs had also been described in previous studies [64,69]. Moreover, N-cadherin, an EMT marker with increased expression in the presence of EMT [73] was not observed in intramucosal foci of SRC [52].…”
Section: Immunohistochemical Profile Of Hdgc and Its Relationship Witsupporting
confidence: 80%
“…These tiny (<0.1 to 10 mm) foci are restricted to the superficial lamina propria and composed of SRCs that are relatively small at the neck-zone level and usually enlarge towards the surface of the gastric mucosa [64].…”
Section: Prophylactic Gastrectomymentioning
confidence: 99%
See 1 more Smart Citation
“…10 -12,14 Apart from the low number of cases analyzed, a single neoplastic lesion was investigated per patient, which constitutes a clear drawback in the analysis, because HDGC is a disease with multiple and apparently unrelated tumor foci, scattered in the stomach of mutation carriers. 15,16 Data from 27 tumors arising in 27 patients from the 13 HDGC families studied so far still indicate CDH1 promoter hypermethylation as the most common 2nd-hit mechanism of inactivation. 10,11,14 In contrast with studies on the 2nd-hit inactivation mechanism of genes causing other neoplastic syndromes, [17][18][19][20] somatic genetic alterations (mutations and loss of heterozygosity [LOH]) of CDH1 were uncommonly found.…”
mentioning
confidence: 99%
“…Several studies have shown that even though CDH1-mutation carriers had negative biopsies before prophylactic gastrectomy, cancer foci were detected in their gastrectomy specimens. 16,17 Management (please describe)…”
Section: How Is the Cost Effectiveness Of Alternative Diagnostic Methodsmentioning
confidence: 99%